Proceedings of the International Conference on Teacher Training and Education 2017 (ICTTE 2017) 2017
DOI: 10.2991/ictte-17.2017.57
|View full text |Cite
|
Sign up to set email alerts
|

Profile of Elementary School Pre-Service Teacher Based on High Order Thinking Skills (HOTS) on Natural Science Subject

Abstract: Scientific inquiry and project-based learning can foster the ability to think, work, and be scientific and communicate it as an important aspect of Life Skills. Science learning emphasizes the provision of direct learning experience through the use and development of process skills and scientific attitudes, so as to empower the high thinking ability of Elementary School Pre-Service Teacher (ESPT). The aim of this study to determine the competence profile of high-order thinking skills (HOTS) ability of 120 pre-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
1
0
2
Order By: Relevance
“…According to Anida et al (2018) teachers also face problems in implementing HOTS assessment in the classroom because they do not understand the meaning of HOTS items. Overall, the finding of this research about the level of knowledge towards HOTS is in line with Atmojo et al (2017), in which the readiness in the aspect of knowledge was still inadequate among pre-service teachers. The findings of this research however, contradict the findings from Mohamad Hisyam et al (2017), Syazana and Zamri (2018), Norshuhada andKamisah (2019), andNursafra et al (2021), in which the level of knowledge among teacher was at a high level.…”
Section: Discussionsupporting
confidence: 81%
“…According to Anida et al (2018) teachers also face problems in implementing HOTS assessment in the classroom because they do not understand the meaning of HOTS items. Overall, the finding of this research about the level of knowledge towards HOTS is in line with Atmojo et al (2017), in which the readiness in the aspect of knowledge was still inadequate among pre-service teachers. The findings of this research however, contradict the findings from Mohamad Hisyam et al (2017), Syazana and Zamri (2018), Norshuhada andKamisah (2019), andNursafra et al (2021), in which the level of knowledge among teacher was at a high level.…”
Section: Discussionsupporting
confidence: 81%
“…Several studies supported the above findings that elementary school preservice teachers' HOTS competence can improve with material reinforcement and learning models that can support their HOTS (Atmojo, et al, 2017). In the study conducted by Malik, et al (2018) revealed that the utilization of a Higherorder Thinking laboratory (HOT-Lab) in enhancing the critical skills of preservice teachers had a greater impact on improving their critical thinking skills on RCL circuit topic.…”
Section: Resultsmentioning
confidence: 82%
“…Topik pembelajaran sistem respirasi manusia dalam mata pelajaran Ilmu Pengetahuan Alam (IPA) sangat berkaitan erat dengan kemampuan HOTS (Atmojo et al, 2017;Nugraha et al, 2020;Zulfiani et al, 2020). Sistem respirasi manusia dalam pembelajaran IPA di Sekolah Dasar (SD) berhubungan dengan kemampuan menganalisis yang harus dimunculkan pada siswa terkait dengan berbagai masalah sistem respirasi yang mungkin saja menyerang manusia.…”
Section: Penelitian Lain Yang Terkait Dengan Hots Adalah Pengembangan...unclassified